2017
DOI: 10.1111/eci.12779
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes are not directly involved in atrial fibrillation: a prospective cohort study

Abstract: The direct relationship between atrial fibrillation and liver enzymes is absent and depends, at least in part, on the progression of heart failure as captured by N-terminal pro-brain natriuretic peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A study of 809 patients with atrial fibrillation on admission out of 5501 CAD patients showed that GGT activity was independently associated with AF (34). However, a prospective study of 1428 men aged 60-79 years of age who developed AF did not show a relationship between AF and change in GGT after adjusting for N-terminal pro-brain natriuretic peptide (35). A study from Korea from a national database of 266,550 people with a mean age of 53 who underwent a national insurance health check up found an increase in AF incidence with increasing quartiles of GGT and after adjusting for BMI the GGT was a good predictor of AF only in the non-obese population (36).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…A study of 809 patients with atrial fibrillation on admission out of 5501 CAD patients showed that GGT activity was independently associated with AF (34). However, a prospective study of 1428 men aged 60-79 years of age who developed AF did not show a relationship between AF and change in GGT after adjusting for N-terminal pro-brain natriuretic peptide (35). A study from Korea from a national database of 266,550 people with a mean age of 53 who underwent a national insurance health check up found an increase in AF incidence with increasing quartiles of GGT and after adjusting for BMI the GGT was a good predictor of AF only in the non-obese population (36).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…19 A number of longitudinal studies have consistently shown that NAFLD, diagnosed by serum levels of liver enzymes, 20,21 surrogate scores (eg, fatty liver index calculated from BMI, GGT, triglyceride, and waist circumference), 22,23 imaging methods (eg, ultrasonography), 24,25 or International Classification of Diseases codes, 26 is significantly associated with incident AF as assessed by ECG, Holter monitoring, or medical record information, independent of several other AF risk factors, despite a few exceptions. [27][28][29] Two cohort studies reported that elevated levels of ALT, AST (aspartate aminotransferase), or GGT were significantly associated with an increased incidence of AF in the general population, and the results remained significant after multivariate adjustment. 20,21 Besides the adjustment for several known cardiometabolic risk factors, the study by Sinner et al 20 further adjusted for cardiac murmur and PR interval, whereas the study by Alonso et al 21 further adjusted for coronary heart disease (CHD), heart failure, and NT-proBNP (N-terminal pro-brain natriuretic peptide).…”
Section: Epidemiological Evidence Linking Nafld To Cardiac Arrhythmia...mentioning
confidence: 99%
“…23 In contrast with these findings, however, a cohort study with a mean follow-up duration of 12.3 years shows that although the risk for incident AF is associated with the change in GGT (OR, 1.18 [95% CI, 1.01–1.37]) after multiple adjustments for cardiometabolic risk factors, the association is lost after further adjusting for baseline levels of ( P =0.088) or changes in ( P =0.40) NT-proBNP. 28 Therefore, further investigation is required to clarify whether the association between liver enzymes and AF depends on the progression of heart failure.…”
Section: Epidemiological Evidence Linking Nafld To Cardiac Arrhythmiasmentioning
confidence: 99%
“…Since reporting that the relationship between incident atrial fibrillation (AF) and the liver enzymes gamma‐glutamyl transferase (GGT), alanine transaminase (ALT) and aspartate transaminase (AST) depends on the progression of heart failure as captured by ΔN‐terminal pro‐brain natriuretic peptide (NT‐proBNP), no other studies reported on AST and ALT. However, the attention moved to GGT .…”
Section: Liver Enzymes Are Not Directly Involved In Atrial Fibrillatimentioning
confidence: 99%
“…Faced with the same risk of stroke, physicians prescribed less to themselves than to patients. X 79 The direct relationship between atrial fibrillation and liver enzymes is absent and depends, at least in part, on the progression of heart failure as captured by N-terminal pro-brain natriuretic peptide. X a Chemerin mRNA and protein were not changed in non-alcoholic steatohepatitis (NASH) liver of very obese patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%